Effect of Tillage on Soil Water Content and Temperature Under Freeze–Thaw Conditions. Issue 1 (4th February 2013) - Parkin, Gary; von Bertoldi, Axel P.; McCoy, Amber J.
Abstract : High resolution (hourly) soil water content and temperature data have been collected for nearly 10 yr within the 0–100 cm depth profiles under no‐till (NT) and conventional fall tillage (CT) practices. The data indicate significant differences between the two tillage practices, especially during winter and early spring freeze\thaw cycles. Results indicate that shallow minimum soil temperatures were lower under CT than NT; however, average winter shallow soil temperatures were very similar between the two treatments. Soil freezing characteristic curves (SFC) measured in situ with soil water content and temperature data were analyzed for differences between treatments as the NT system matured. The SFC shapes for NT evolved over a 7‐yr period as the age of the NT system increased. An intensive freeze–thaw episode showed strong hysteresis in SFC, a phenomenon not analyzed in detail before this study based on data collected in the field.